The Two-thirds Gender Rule ‘Mirage’: Unlocking the Stalemate - Ongoya, Elisha (Strathmore Law Journal, 2021)
Today we talk about the principle of gender inclusivity in Kenya’s governance framework.1 I thank the administration of the Mombasa Law Campus of the University of Nairobi for giving me an opportunity to address its academic community on the subject. I thank the Mombasa Law Society, the oldest law society in this country, for partnering with the University of Nairobi, Mombasa Campus, on this worthy course. Partnerships between industry and the academy are always a worthy venture. The choice of topic today is both germane and misleading. The journey towards a more inclusive society in Kenya has been a rather long one. On 9 March 2018, the key protagonists in Kenya’s political space, President Kenyatta and former Prime Minister Raila Odinga recognised inclusivity as one of the nine-point agenda towards building bridges in Kenya. The aspect of inclusivity called gender inclusivity has also had a longwinded history. There is no possibility of me capturing the story of this journey fully and justly in today’s presentation alone. I will, therefore, focus on a very small aspect of this journey, that is, the cases that I have had the privilege of history to walk through as an advocate.